Sorption of tetrabromobisphenol A onto microplastics: Behavior, mechanisms, and the effects of sorbent and environmental factors - Li, Shengsheng; Ma, Ruixue; Zhu, Xiaohui; Liu, Chang; Li, Liangzhong; Yu, Ziling; Chen, Xichao; Li, Zongrui; Yang, Yan (Ecotoxicology and environmental safety, 2021)
Microplastics (MPs) and halogenated organic pollutants coexist in ambient water and MPs tend to sorb organic pollutants from surrounding environments. Herein, a study on the sorption behavior of tetrabromobisphenol-A (TBBPA) onto four different MPs, namely, polyethylene (PE), polypropylene (PP), polystyrene (PS), and polyvinyl chloride (PVC) was carried out. Effects of MPs properties and environmental factors, including the type, surface charge and pore volume as well as the ionic strength (Ca2+) and humic acid (HA) on the sorption of TBBPA were discussed. Results showed that the sorption of TBBPA onto the MPs could reached an equilibrium within 24 h, and the sorption capacities decreased in the following order —PVC (101.85 mg kg-1) >PS (78.95 mg kg-1) >PP (58.57 mg kg-1) >PE (49.43 mg kg-1). Adsorption kinetics data fitted by intraparticle diffusion model revealed both surface sorption and intraparticle diffusion contributed, in the interfacial diffusion stage approximately 11–29% of TBBPA slowly diffused onto the surface of the MPs, and finally, in the intraparticle diffusion stage. The increase of Ca2+ concentration could promote the sorption of TBBPA by PE, PP, and PS, but no significant alteration for PVC. For all the four MPs, HA was found to exert a negative effect on TBBPA sorption. The adsorption was mainly driven by hydrophobic partition and electrostatic interactions. [Display omitted] •TBBPA sorption behaviors on four MPs (PE, PP, PS and PVC) were investigated.•Polyvinyl chloride (PVC) exhibited the highest sorption capacity for TBBPA.•TBBPA adsorption was mainly driven by hydrophobic and electrostatic interactions.•The sorption capacity of PVC was almost not affected by ionic strength of solution.